Strategi peningkatan peran Pemangku Kepentingan dalam mengatasi Masalah Keuangan - Adi Suwarno, Suparjo; Anis Sulalah, Asia (at-Tahsin, 2023)
The financing problem is a classic problem that is still the main enemy of educational institutions. Funding that is not managed well will give rise to new problems and is vulnerable to hampering educational programs that have been created. This research aims to discuss qualitative research methods for literature study. The method used is library research, collecting data by searching for sources and reconstructing them from various sources such as books, journals and existing research.This article presents the concept of managing and raising educational funds (fundraising) which can be applied by educational institutions as an alternative to exploring financial resources in addition to using financial resources from the government and school/madrasah committees.